Предмет: Алгебра,
автор: Альбина1609
Разложите на множители
(a-b)+3a-3b
Ответы
Автор ответа:
0
(a-b)+3 (a-b=(a-b)(1+3)
Автор ответа:
0
Там в первом примере
Автор ответа:
0
(a-b)+3 (a-b)
Автор ответа:
0
Не уверена, но думаю, что так :)
(а-b)+3a-3b=(a-b)+3(a-b)=4(a-b)
(а-b)+3a-3b=(a-b)+3(a-b)=4(a-b)
Похожие вопросы
Предмет: Биология,
автор: victoriamay66
Предмет: Русский язык,
автор: gulnaznizamova01
Предмет: Литература,
автор: Marina16102008
Предмет: История,
автор: marado1199
Предмет: Литература,
автор: atevs1809